Haemolytic uraemic syndrome in children admitted to a rural district hospital in Kenya. - Olotu, A; Mithwani, S; Newton, C (2008)
We studied children admitted to Kilifi District Hospital, Kenya, between 1997 and 2005 with haemolytic uraemic syndrome (HUS) and reviewed their records in order to determine the clinical features and outcomes of the disease. Thirty-one children fulfilled the criteria: 21 (68%) had diarrhoea-associated HUS (D + HUS), the remainder did not (D-HUS); five had involvement of the central nervous system. Those with D-HUS had lower haemoglobin and platelet counts when compared with those with D + HUS. The overall mortality rate was 55% (17/31) with no significant difference between the two groups. Severe hyponatraemia ([Na(+)] <120 mmol/L) predicted a poor outcome. Shigella dysenteriae was the most common isolated organism in the stool and Escherichia coli and S. dysenteriae were the most common blood isolates. HUS carries a high mortality rate and D-HUS is as common as D + HUS.